PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI, DAN KEPUASAN KERJA TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR - Fransisca Hani Cahyaningrum, Sri Lestari Triyaningsih & Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2014)
The purpose of this study were to analyze: (1)the significance of the influence of organizational commitment, organizational culture, and job satisfaction on Organization Citizenship Behavior, (2) the influence of the dominant variables of the Organization Citizenship Behavior on the employees of PT ATMI Surakarta. The method of research used survey method, the population in this study were permanent employees of PT ATMI Surakarta, amounting to 335 people. In a study using a sampling technique proportional random sampling, number of samples used by 67 people. From this analysis, the variables were dominant influence on Organization Citizenship Behavior on the employees of PT ATMI Surakarta is organizational culture variables. T test results: variable organizational commitment, organizational culture, job satisfaction significantly affects the organization Citizenship Behavior. Test Results F is obtained probability value of 0,000 then the model used to test the effect of independent variables, namely organizational commitment, organizational culture and job satisfaction on the dependent variable is Organization Citizenship Behavior is right. The test results obtained by the value of the coefficient of determination Adjusted R Square = 0,716 means it is known that the effect provided by the independent variable of organizational commitment, organizational culture and job satisfaction on the dependent variable is Organization Citizenship Behavior on the employees of PT ATMI Surakarta 71,6 percent. Keywords: organizational commitment, organizational culture, job satisfaction and Organization Citizenship Behavior